2013
DOI: 10.1371/journal.pone.0079686
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Exercise and Conjugated Linoleic Acid (CLA) Supplementation Up-Regulate CYP17A1 and Stimulate Testosterone Biosynthesis

Abstract: A new role for fat supplements, in particular conjugated linoleic acid (CLA), has been delineated in steroidogenesis, although the underlying molecular mechanisms have not yet been elucidated. The aims of the present study were to identify the pathway stimulated by CLA supplementation using a cell culture model and to determine whether this same pathway is also stimulated in vivo by CLA supplementation associated with exercise. In vitro, Leydig tumour rat cells (R2C) supplemented with different concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 41 publications
(51 reference statements)
2
54
0
1
Order By: Relevance
“…Western Blotting analyses of protein cell lysates and immunoprecipitates were performed as previously described [25]. Briefly, 40 μg of proteins from cell lysates or 500 μg from immunoprecipitates were added to 4× Laemmli buffer and heated for 5 min at 95°C.…”
Section: Western Blottingmentioning
confidence: 99%
“…Western Blotting analyses of protein cell lysates and immunoprecipitates were performed as previously described [25]. Briefly, 40 μg of proteins from cell lysates or 500 μg from immunoprecipitates were added to 4× Laemmli buffer and heated for 5 min at 95°C.…”
Section: Western Blottingmentioning
confidence: 99%
“…It has been established that Hsp60 is actively secreted by human tumor cells and, thus, have potential as useful cancer biomarkers properties [29,40]. Hsp60 can be released from cells in free, soluble form, possibly via Golgi participating in extracellular molecular interactions and cell signaling, acting as a paracrine factor when released into the medium [3,40].…”
Section: Discussionmentioning
confidence: 99%
“…The qRT-PCR technique was performed as previously described [29]. Briefly, total cellular RNA was isolated from both control and treated cell cultures, using TRIzol ® REAGENT (Sigma-Aldrich) and according to the manufacturer's instructions.…”
Section: Real-time Quantitative Pcr (Qrt-pcr)mentioning
confidence: 99%
“…And Macaluso et al 24 reported that there were no significant differences in total body mass, BMF, and LBM by CLA supplementation, 6 g/day for Reduced body fat mass by CLA intake suggested that CLA causes reduction in lipid uptake by adipose cells because of an effect on lipoprotein lipase and stearoyl-CoA desaturase and carnitine palmitoyltransferase activity in muscle cells, which is the rate-limiting enzyme in β-oxidation, is increased 18 . On the other hand, increased muscle mass by CLA intake was suggested by increased serum testosterone level 15,24,27 . Testosterone can induce increase of energy expenditure by elevating mitochondrial biogenesis in skeletal muscle in mice 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Barone et al 27 reported that trained mice showed an increase in free plasma testosterone and an upregulation of 17α-hydroxylase/17, 20-lyase CYP17A1 mRNA and protein. The effect of training on CYP17A1 expression and testosterone biosynthesis was significantly higher in the trained mice supplemented with CLA compared with placebo.…”
Section: Discussionmentioning
confidence: 99%